Ø·Ø±ÙŠÙ‚Ø© ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„Ù‘ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - ilham Nur Kholiq; Arika Nasiroh (Institut Agama Islam Darusssalam Blokagung, 2021)
This study aims to describe the method used by the teacher in teaching Arabic and the factors that support and hinder the learning process of Arabic, especially in Madasah Aliyah al Amiriyyah Blokagung Tegalsari Banyuwangi. And this type of research is field research (field research) and this research is classified as qualitative descriptive research. The subjects in this study were Arabic teachers, students and principals. Data collection techniques using observation, interviews, and documentation.Based on the observations made by the author on the Arabic Language Learning Medote applied at Madrasah Aliyah al Amiriyyah, it can be concluded that the methods applied by the Arabic teacher at Madrasah Aliyah are: translation method qiro'ah method direct method, audio visual method and mixed methods. As for the inhibiting factors in learning, namely: different backgrounds of students, students who are less active in participating in learning Arabic, and Madrassas whose facilities are lacking in the learning process. Supporting factors in learning are students' high interest in learning Arabic and a comfortable environment for the learning process.